Were the deccan flood basalts derived in part from ancient oceanic crust within the indian continental lithosphere? - SHETH, HC (Gondwana Research, 2005)
Deep mantle plumes supposedly incorporate deeply subducted eclogitized oceanic crust, and continental flood basalts (CFBs) are now thought by some to be derived from such eclogite-bearing peridotite plumes. Eclogite-peridotite mixtures have much lower solidi (and produce much greater melt fractions for a given temperature) than peridotite. Ferich (eclogite- or pyroxenite-bearing) sources have been inferred for many CFBs. However, plumes with considerable amounts of eclogite should have difficulty in upwelling owing to the high density of eclogite. Besides, CFBs are always located along pre-existing lithospheric structures (suture zones, edges of thick cratons) and commonly associated with lithospheric rifting and continental breakup. India ' s major late Mesozoic CFB, the Deccan Traps, erupted through rift zones and a new continental margin that had developed along ancient suture zones traversing the subcontinent. Many Deccan basalts are too Fe-rich to have been in equilibrium with a peridotite mantle source, and have commonly been considered to be significantly fractionated derivatives of picritic liquids. However, it is possible to view them as relatively less evolved liquids derived from a source with extra fertility (i.e., an Fe-rich source). A new non-plume, plate tectonic model for Icelandic hotspot volcanism involves melting of a shallowly recycled slab of eclogitized Iapetus oceanic crust formerly trapped along the Caledonian suture. The model explains the geochemical-petrological characteristics of Icelandic basalts, and is consistent With passive upper mantle upwelling under Iceland inferred from recent seismic tomography. Based on the petrological and geochemical features of the Deccan flood basalts of the type section, in the Western Ghats, I propose that old, eclogitized oceanic crust trapped in the ancient Indian suture zones could have produced voluminous. basaltic melts during the Deccan event.